2002
DOI: 10.21273/hortsci.37.7.1103
|View full text |Cite
|
Sign up to set email alerts
|

Development of Bt-cry5 Insect-resistant Potato Lines 'Spunta-G2' and 'Spunta-G3'

Abstract: The potato tuber moth (Phthorimaea operculella Zeller) is the primary insect pest of cultivated potato (Solanum tuberosum L.) in tropical and subtropical regions, causing both foliar and tuber damage. In contrast, the Colorado potato beetle (Leptinotarsa decemlineata Say) is the most important insect pest in the northern potato production latitudes. The codon-modified Bacillus thurin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…The bioassay method used was based on the assumption that the level of Cry protein in excised leaves was similar to that in the foliage of intact plants. The same assumption has been made in similar studies involving PTM bioassays (Ebora et al, 1994;Jansens et al, 1995;Westedt et al, 1998;Beuning et al, 2001;Douches et al, 1998Douches et al, , 2002Li et al, 1999;Davidson et al, 2002Davidson et al, , 2004, and has been validated by the observed high correlation between excised leaves and intact plants for growth of PTM larvae in response to cry gene expression (Davidson et al, 2002).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The bioassay method used was based on the assumption that the level of Cry protein in excised leaves was similar to that in the foliage of intact plants. The same assumption has been made in similar studies involving PTM bioassays (Ebora et al, 1994;Jansens et al, 1995;Westedt et al, 1998;Beuning et al, 2001;Douches et al, 1998Douches et al, , 2002Li et al, 1999;Davidson et al, 2002Davidson et al, , 2004, and has been validated by the observed high correlation between excised leaves and intact plants for growth of PTM larvae in response to cry gene expression (Davidson et al, 2002).…”
Section: Discussionmentioning
confidence: 55%
“…In potato, it is often desirable to couple high-level expression of the transgene in foliage with no expression in tubers. Constitutive promoters have been used to drive cry gene expression in all previous studies targeting PTM resistance in transgenic potatoes (Douches et al, , 2002Jansens et al, 1995;Cañedo et al, 1999;Li et al, 1999;Chakrabarti et al, 2000;Mohammed et al, 2000;Davidson et al, 2002Davidson et al, , 2004. Since PTM generally infests foliage of potato crops prior to the tubers (Foot, 1979), preventing foliar infestation may be sufficient to avoid tuber infestation.…”
Section: Discussionmentioning
confidence: 99%
“…Relatively high level of B.t. protein expression with better PTM control could be achieved by using codon modified and truncated cry1Ac9 (Beuning et al 2001;Davidson et al 2002), cry 1Ia1 (Mohammed et al 2000;Douches et al 2002), and a hybrid Bt toxin (SN19) gene consisting of domain I and III of cry1Ba and domain II of cry1Ia (Naimov et al 2003). Gleave et al cloned and sequenced a B.t.…”
Section: Introductionmentioning
confidence: 99%
“…However, with the advent of genetic engineering, genes for insect resistance can be transferred into plants to develop insectresistant plants. Transgenic potatoes that express cry genes derived from various strains of the soil bacterium Bacillus thuringiensis (Bt) have exhibited resistance to PTM (Jansens et al 1995;Cañedo et al 1999;Li et al 1999;Chakrabarti et al 2000, Douches et al 2002Davidson et al 2002Davidson et al , 2004Meiyalaghan et al 2005Meiyalaghan et al , 2006aHagh et al 2009;Jacobs et al 2009;Kumar et al 2010).…”
Section: Introductionmentioning
confidence: 99%